(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
In the context of globalization, market relations are becoming increasingly complex, turning into a system deeply integrated into the world economy, multifaceted and characterized by a high level of uncertainty. Factors such as the economic policies of states, financial flows, consumer behavior and technical progress have a significant impact on the balance of international markets, which requires studying various theoretical approaches to market relations and their scientific analysis. The development of mechanisms to improve the efficiency of modern economic systems and the development of solutions based on comprehensive and systemic approaches to solving problems of market relations have become a pressing scientific problem of modern research. Therefore, this article analyzes the concept of the market, its types, the main factors of its emergence, the stages of formation and development of market relations on an economic and theoretical basis. The study will provide an in-depth scientific analysis of theoretical and conceptual approaches and methodological solutions to market relations of economic schools that arose at important theoretical turning points in the evolution of economic thought.